Formal Analysis of “Luk Lor -Luk Khat” in Thai Classical Music: A Case Study of Phleng Khamen Rajaburi - Chonpairot, Jarernchai (วิพิธพัฒนศิลป์, 2021)
Abstract This paper investigates the overall formal and internal design of luk lor-luk khat, a type of composition using imitative and contradictory musical techniques. The author collected documents from both Thai and Western sources, including the three main books on Thai classical music: Thai Classical Music Book 1, Book 2, and Book 3 by Montri Tramōd and others. They contain a large Thai classical repertoire, especially phleng sam chan (the composition of the third variation) with luk lor-luk khat style, which refers to a composition using imitative and contradictory musical techniques. The author selected Khamen Rajaburi, Third Variation, Section 1, for analysis because it contains many luk lor-luk khat techniques. The results showed that Khamen Rajaburi was composed according to an overall design similar to the rondo form in Western classical music, whereas its internal form, especially the luk lor-luk khat session (Luk lor-luk khat is a musical pattern in which two groups of instruments interact while playing a particular musical phrase: luk lor referring to the action of the chasing group of instruments which imitate the exact musical phrase played by the fleeing group, whereas luk khat means the chasing group contradicts the musical phrase played by the fleeing group.), is akin to fugue. Fugue is an imitative technique using two voices represented by two groups of instruments, of higher and lower pitch, imitating a longer and a shorter passage. Finally, the two groups of instruments catch up with each other, as the full paper will show. Keywords: formal analysis, luk lor-luk khat, Thai classical piece, formal design